Architecture and landscape design : an investigation into the harmonising of these two aspects of design as exemplified by the collaboration of Gertrude Jekyll and Sir Edwin Landseer Lutyens - Judge, Stephen Michael (Rhodes University, Faculty of Humanities, Department of Fine Art, 1996)
Sir Edwin Lutyens and Miss Gertrude Jekyll were part of the 'Art's and Crafts' movement, which advocated the use of local techniques and materials. They grew up separately, both in the Surrey country-side and both among creative people. Jekyll later worked with Edward Hudson (the author of 'Country Life') who persuaded her to be a garden designer . Lutyens was inspired first by the architecture of Surrey (mostly that of Norman Shaw), then by his friend, Herbert Baker, at architectural school, and lastly, by his long - time partner Jekyll. Munstead Wood, Surrey, England, was the partners' first project and it embodies nearly all of their ideals; the natural and indigenous use of flowers and plants, with an ordered colour scheme ; graded colour schemes without discord; the use of entirely local materials ; the sole use of local craftsmen and local techniques; a garden of 'rooms'; the intergration of architecture and garden design. A revival of interest in the partners work has helped to recreate some of the lost gardens of Jekyll. This interest has in turn put a spotlight on the ideals employed by the partners. Their wide influence has also produced many great buildings and gardens, most notably through the work of Sir Herbert Baker in South Africa. The Union Buildings are a perfect example of Baker's work, and much of it has the stamp of Lutyens' style and ideals. Through my own interest in Lutyens and Jekyll I have created my own Jekyll-style border in Grahamstown, Eastern Cape, to try and prove that her ideals can be translated into climates other than that of England. In this experiment, I succeeded in using indigenous South African plants and flowers with a colour scheme in the style of Jekyll, proving that the ideals to which she aspired could be applied in other countries.
Keywords: Lutyens, Edwin Landseer, Sir, 1869-1944; Jekyll, Gertrude, 1843-1932; Gardens -- Design; Architecture, British